PELAKSANAAN PEMBELAJARAN IPS DI KELAS BERPROGRAM PENDIDIKAN INKLUSI DI SMP NEGERI 31 SEMARANG - Pratiwi, Nor Indah; Lestari, Puji (SOSIOLIUM : Jurnal Pembelajaran IPS, 2020)
SMP Negeri 31 Semarang is one of the schools that implements an inclusive education system, an education system that requires all children with disabilities to be served at the nearest school and in regular classes with their peers. Social studies subjects are one of the subjects that affect children with special needs in inclusive classes because they can help develop the potential of students to be sensitive and responsive to their environment. The method used in this research is descriptive qualitative method. The results of this study indicate that (1) The social studies learning process in the inclusion class includes planning, implementation and evaluation according to the needs and conditions of children with special needs in each inclusive class. 2) Problems encountered by social studies teachers in implementing the learning process in the inclusive class at SMP Negeri 31 Semarang: Social studies teachers do not have special abilities in dealing with children with special needs, and there is only one special tutor available. (3) Efforts in solving problems in the form of providing motivation and constructive messages for students and relying on special supervisors. SMP Negeri 31 Semarang is one of the public schools in Semarang City that is able to implement an inclusive education system. Inclusion schools require that all children with disabilities be served at the closest schools, in regular classes with their peers. Social studies subjects are one of the subjects that affect children with special needs in inclusive classes because they can basically help develop the potential of students to be sensitive and responsive to their environment and social problems that occur in society, especially for children with special needs. The objectives of this study were: (1) Describing the learning process in the inclusive class in the Social Studies subject at SMP Negeri 31 Semarang. (2) Exploring the problems encountered by social studies teachers in the learning process in the inclusion class in the Social Studies subjects at SMP Negeri 31 Semarang. ) Knowing the efforts made by social studies teachers in overcoming problems that occurred in the inclusion class of SMP Negeri 31 Semarang. The method used in this research is descriptive qualitative method with data collection techniques using observation, interviews and documentation. The location of this research is SMP Negeri 31 Semarang. The subjects of this study were school principals, social studies teachers and special supervisors. The validity test in this study used the triangluation of sources and techniques. The data analysis technique of this research uses the stages of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that (1) The social studies learning process in the inclusion class uses different lesson plans to balance the needs of children with special needs. At the preliminary and concluding stages there are no special activities. The materials for the inclusion class are summarized into simpler terms, the models, methods and media used are adjusted. Learning sources for student textbooks, the internet and the environment, while special sources for children with special needs include piano, drums, computers, sewing machines and others. The evaluation is carried out by social studies teachers in different ways but still maintains the KKM set by the school, namely 70. (2) Problems encountered by social studies teachers in implementing the learning process in the inclusion class of SMP Negeri 31 Semarang: Social studies teachers do not have special abilities in dealing with children with special needs, limited learning media, and only one assessment and availability of special supervisors. (3) Efforts in solving problems in the form of providing motivation and constructive messages for students and relying on special supervisors.